Estimating Urban Poverty Consistently Across Countries - Combes, Pierre-Philippe; Nakamura, Shohei; Roberts, Mark; Stewart, Benjamin (Washington, DC : World Bank, 2022)
Global poverty monitored by the World Bank for the Sustainable Development Goals (SDGs) is reported only at the national level, lacking a breakdown between urban and rural areas. A key challenge to producing globally comparable estimates of urban poverty is the need for consistent definitions of urban areas and poverty. This note illustrates an innovative approach to integrating globally consistent urban and poverty measurements to estimate urban poverty statistics that are directly comparable across countries. Two approaches to quantifying urban, the Degree of Urbanization and the Dartboard approaches are applied in seven case countries. By combining these delineations with official household budget survey data, poverty is estimated with international poverty lines. The empirical illustrations demonstrate that the proposed approach is potentially useful to improve the monitoring of global poverty.